ISLAMIC THEOLOGY AND GENDER: REFLECTIONS ON MUHAMMAD SHAHRUR’S THOUGHTS - Afandi, Rachmat (Journal of Islamicate Studies, 2020)
This paper is a study of the thoughts of Muhammad Syahrur with a focus on issues of Islamic theology and gender. Starting from his observers of the problems that occur in Muslims in particular, the application of modernity that is difficult to apply. This difficulty for Syahrur is inseparable from the existence of turath which has become a fixed price so that the existence of ijtihad suffered a setback and as a result of this attitude Muslims are unable to filter and reinterpret Islamic teachings that are able to coincide with modernity. On this basis, Syahrur came by bringing a movement of change aimed at re-interpreting the messages contained in the Koran. Besides this movement was carried out to eradicate the fantasy of turath which makes it difficult for Islam to progress. The scientific framework to support this movement is based on Linguistic theory which according to the language does not have the same language. On this basis, Syahrur said that if Islamic scientific traditions in the past could not be applied and the final form of Syahrur's opinion wanted a scientific Islam. From this scientific Islam was born a new thought of the concepts of Islamic theology and gender which had been considered irrelevant to face the challenges of modernity so that the concept of Islamic theology was universal, progressed and in its development could be accepted by every human being.